الأسلوبية والأسلوب: المنهج والمصطلح – مقاربة في ضوء نقد النقد - رملي, هديل (جامعة الوادي - university of eloued, 2023)
بعد الدراسة المطولة لكتاب الاسلوبية والاسلوب استنتجنا أن: - علم الاسلوب علم حديث النشأة يسعى الى كسب استقلاله عن العلم الام الذي هو الالسنية. - يعرف الاسلوب بالتفكير ويختلف باختلاف انماطه. - علم الاسلوب هو مجوعة الطاقات الايحائية المترجمة في الخطاب الادبي. - النقد الحديث اصبح نقدا خادما للأسلوب وصار فرعا من فروع الاسلوبية. - الاسلوبية ذات نظرية شمولية. - تعرف الاسلوبية بداهة بالبحث عن الاسس الموضوعية لإرساء علم الاسلوب. After a long study of the book stylistics and style, we concluded that: - Stylistics is a newly emerging science that seeks to gain independence from the mother science, which is the Sunnism. - Style is known as thinking and varies according to its patterns. - Stylistics is the set of suggestive energies translated into literary speech. - Modern criticism has become a criticism of style and has become a branch of Stylistics. - Stylistics has a holistic theory. - Stylistics is defined a priori by the search for objective grounds for establishing the science of style.
نقد ومناهج
Keywords: الأسلوبية، الأسلوب، المنهج، المصطلح، نقد النقد.; Stylistics, style, method, idiom, criticism of criticism